The Usability, Acceptability, and Performance of the Maternal PPH Wrap Device in Controlling Postpartum Hemorrhage: A Pilot Study at Kawempe National Referral Hospital, Uganda - Solomon C. Owino; Maureen D. Etuket; Owen Muhimbise; Martin Kiwanuka; Beryl N. Arinda; Denis Mukiibi; Noah Kiwanuka; Robert T. Ssekitoleko; Sam Ononge (IEEE Journal of Translational Engineering in Health and Medicine, 2022)
Timely intervention for atonic postpartum hemorrhage (PPH) significantly reduces the incidence of death from PPH. However, technological solutions geared towards this have not received substantial adoption by the health community in sub-Saharan Africa due to limiting factors such as; cumbersome application, being costly, requiring skilled personnel, needing cold chain storage, and the associated side effects. This pilot study aimed to assess the usability, acceptability, and performance of the Maternal PPH Wrap, a first-aid device designed to control atonic PPH after childbirth. Forty subjects were recruited for the study. Twenty of these were women who sought maternity care at Kawempe National Referral Hospital (KNRH). The women wore the device for 120 minutes while their vitals were recorded every 20 minutes. The device’s acceptability and performance were evaluated on the women. The remaining twenty were licensed midwives working at KNRH. The device’s usability was assessed on all the midwives recruited for the pilot study using a usability questionnaire. There was a non-significant reduction in blood loss associated with the use of the Maternal PPH Wrap alongside the standard of care as opposed to the standard of care alone. This reduction in blood loss was detected between the $80^{th}$ and $120^{th}$ minute of the device application onto the mothers. The acceptability and usability scores from the study participants also scored favorably. The Maternal PPH Wrap demonstrated potential to control PPH and product satisfaction, and these results will support the device’s redesign leading into a phase I clinical trial.